ANALISIS KETIMPANGAN PEMBANGUNAN REGIONAL WILAYAH KABUPATEN/KOTA PROVINSI SULAWESI TENGGARA TAHUN 2016-2020 - Miktoni Lahagu; Rostin Rostin; Samsul Barani (JEP (Jurnal Ekonomi Pembangunan), 2022)
The purpose of this study was to determine the level of regional development inequality in the regency/City of southeast Sulawesi Province. The analytical tool used is quantitative in the from of descriptive data analysis and secondry data with the Williamson Indeks analysis method, which is to compare the level of per capita income and population during 2016-2020. Based on the result of calculations using the Development Inequalty Analysis, it fluctuates and decreases, in 2016 it has an inequality of 0.99 while in 2020 it has decreased by o.88. however, if the data are averenged, the regional development inequality level of the regency/city of southeast Sulawesi Provinceis in the range of the high development inequality level category From year to year. And the factor that cause inequality are the increasing number of people who are increasing but the available business fields are still inadequate so that the low level of community income will affect the inequality of development. In addition, the management of natural resource content, demographic conditions, smooth mobility of goods and services, developing all the potensials in each sector and so on can be a solution to reduce development inequality in the disctricts/cities of southeast Sulawesi Province.